Early postpartum pharmacokinetics of lopinavir initiated intrapartum in Thai women - Cressey T.R. (2014)
Lopinavir (LPV) exposure is reduced during the third trimester of pregnancy. We report the pharmacokinetics of standard LPV-ritonavir dosing (400/100 mg twice daily) in the immediate and early postpartum period when initiated during labor. In 16 human immunodeficiency virus-infected Thai women, the median (range) LPV area under the concentration-time curve and maximum and minimum concentrations in plasma were 99.7 (66.1 to 180.5) μg·h/ml, 11.2 (8.0 to 17.5) μg/ml, and 4.6 (1.7 to 12.5) μg/ml, respectively, at 41 (12 to 74) h after delivery. All of the women attained adequate LPV levels through 30 days postpartum. No serious adverse events were reported. Copyright © 2009, American Society for Microbiology. All Rights Reserved.